Application of Challenge Based Learning Model to Students' Critical Thinking Ability in Fiqh Learning - Wahyu Kusuma Mukti; Langputeh, Sukree; Muhamad Fauzi; Achmad Fadil; Irja Putra Pratama; Aristophan Firdaus (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aimed to investigate the application of the Challenge Based Learning (CBL) model in improving students' critical thinking skills in Fiqh learning. The CBL model utilizes environmental challenges as a learning resource. This quantitative study employed tests, observation, and documentation to collect data. Data analysis was conducted using descriptive statistics and the